2021
DOI: 10.1021/acs.langmuir.1c01204
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Quorum Sensing Signals Promote Large-Scale Remodeling of Lipid Membranes

Abstract: We report that N-acyl-L-homoserine lactones (AHLs), a class of nonionic amphiphiles that common bacteria use as signals to coordinate group behaviors, can promote largescale remodeling in model lipid membranes. Characterization of supported lipid bilayers (SLBs) of the phospholipid 1,2-dioleoylsn-glycero-3-phosphocholine (DOPC) by fluorescence microscopy and quartz crystal microbalance with dissipation (QCM-D) reveals the well-studied AHL signal 3-oxo-C12-AHL and its anionic head group hydrolysis product (3-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(65 citation statements)
references
References 79 publications
8
57
0
Order By: Relevance
“…Daniels et al also demonstrated that some long-chained AHLs can self-assemble and undergo phase changes when compressed at air–water interfaces . Finally, recent reports have demonstrated that AHLs can intercalate into lipid membranes, , allowing them to translocate across lipid bilayers, promote membrane depolarization, dissolve lipid phases, and, of particular interest to the work reported here, promote large-scale membrane remodeling . These studies reveal that both head-group and aliphatic tail structure can have substantial impacts on the behaviors of AHLs, including self-association in solution , and adsorption , and subsequent multiscale phenomena ,, that occur when they come in contact with lipid bilayers.…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…Daniels et al also demonstrated that some long-chained AHLs can self-assemble and undergo phase changes when compressed at air–water interfaces . Finally, recent reports have demonstrated that AHLs can intercalate into lipid membranes, , allowing them to translocate across lipid bilayers, promote membrane depolarization, dissolve lipid phases, and, of particular interest to the work reported here, promote large-scale membrane remodeling . These studies reveal that both head-group and aliphatic tail structure can have substantial impacts on the behaviors of AHLs, including self-association in solution , and adsorption , and subsequent multiscale phenomena ,, that occur when they come in contact with lipid bilayers.…”
Section: Introductionsupporting
confidence: 70%
“…Calcein-loaded LUVs were prepared using a previously described freeze–thaw and vesicle extrusion procedure. , In brief, DOPC dissolved in chloroform was aliquoted into vials, and the chloroform was subsequently removed under a stream of N 2 and further dried under vacuum for at least 1 h. A 70 mM calcein solution in buffer was then added to the dried lipids and vortexed vigorously to form a turbid 5 mg/mL DOPC solution. The calcein-containing solution was prepared by massing an appropriate amount of calcein, to which buffer was added and the pH of the solution was adjusted to 7.4 with 10 M NaOH.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations